The Role of Public-Private Partnerships in Strengthening Agrocomplex Systems in Indonesia's Economic Corridors - Mutmainna, Mutmainna (Journal of Agro Complex Development Society, 2025)
This study analyzes the role of public-private partnerships in strengthening agrocomplex systems in Indonesia's economic corridors using a mixed-methods approach involving in-depth interviews, FGDs, surveys, and document analysis. The results show significant variation in the implementation of partnership models across economic corridors, with the multi-stakeholder consortium model showing the highest level of satisfaction among farmers. Public-private partnerships contributed to an average increase in productivity of 23.7 % and farmer income of 30.5% compared to non-partner farmers. Critical factors for partnership success include transparency in the use of funds , clarity of risk-sharing mechanisms, and the presence of a neutral facilitator. Key challenges to partnership implementation include unequal bargaining power (76.5 % ), unclear legal framework (67.8%), and limited supporting infrastructure (63.4%). The study highlights the importance of a contextual approach in partnership development, strengthening the governance dimension, and innovating financing models to enhance the positive impact of partnerships on sustainable agricultural development in Indonesia. The study findings provide important policy implications for the development of inclusive and sustainable agrocomplex systems across Indonesia's economic corridors.